2011
DOI: 10.1021/ic2010858
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of a {Re63-S)8} Core-to-Ligand Charge-Transfer Excited State in an Octahedral Hexarhenium Complex

Abstract: A new complex, [Re(6)S(8)Cl(5)ppy](3-) (ppy = 4-phenylpyridine), was synthesized and characterized. The complex showed red emission at 296 K in both the crystalline phase and CH(3)CN. The transient absorption spectrum of [Re(6)S(8)Cl(5)ppy](3-) revealed that the emissive excited state involved the {Re(6)(μ(3)-S)(8)} core-to-ligand charge-transfer character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…For comparison, the spectroscopic and photophysical data of {Re 6 Se 8 } 2+ cluster core‐based complexes with anionic terminal ligands (cyanide and isothiocyanate) in acetonitrile are included in Table 3. As can be seen from Table 3, although the emission from [Re 6 Se i 8 (N 3 ) a 6 ] 4– in acetonitrile is weaker and shifted to the shorter wavelength compared with that of [Re 6 Se i 8 (CN) a 6 ] 4– or [Re 6 Se i 8 (NCS) a 6 ] 4– , [Re 6 Se i 8 (N 3 ) a 6 ] 4– exhibits comparable lifetime, demonstrating that the emissive excited state of the complex is localized on the {Re 6 Se 8 } core similar to those of the majority of Re 6 cluster complexes hitherto reported 23j…”
Section: Resultssupporting
confidence: 53%
“…For comparison, the spectroscopic and photophysical data of {Re 6 Se 8 } 2+ cluster core‐based complexes with anionic terminal ligands (cyanide and isothiocyanate) in acetonitrile are included in Table 3. As can be seen from Table 3, although the emission from [Re 6 Se i 8 (N 3 ) a 6 ] 4– in acetonitrile is weaker and shifted to the shorter wavelength compared with that of [Re 6 Se i 8 (CN) a 6 ] 4– or [Re 6 Se i 8 (NCS) a 6 ] 4– , [Re 6 Se i 8 (N 3 ) a 6 ] 4– exhibits comparable lifetime, demonstrating that the emissive excited state of the complex is localized on the {Re 6 Se 8 } core similar to those of the majority of Re 6 cluster complexes hitherto reported 23j…”
Section: Resultssupporting
confidence: 53%
“…, where L was pyridine (py) or its derivatives, namely 4-methylpyridine (mpy), 4-phenylpyridine (ppy), 4,4Ј-bipyridine (bpy) or pyrazine (pz). [75,77,79] It was found that the complex with py, mpy, or ppy is characterized by significantly higher quantum yield and a longer lifetime than the relevant value of the complex with bpy or pz, i.e. the complexes with ligands having a free nitrogen end and a small pK a value [pK a (bpy) = 4.44 or pK a (pz) = 0.65].…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…We reported previously, on the other hand, that hexarhenium(III) clusters, [Re 6 (l 3 -S) 8 X 6 ] 4-(X = Cl -, Br -, I -, and so forth), showed relatively intense room temperature emission in the visible * near infrared region (600-1,000 nm) with the emission lifetime (s) and quantum yield (U) in acetonitrile being s = 4-11 ls and U = 0.015-0.056, respectively [8] [15], N-heteroaromatics [16][17][18][19][20][21], phosphine derivatives [17,18,22,23], HCOO [24], CH3COO [25], and N 3 [26] [8,29]. Acetonitrile (Wako Pure Chemicals Co. Ltd.) as a medium throughout the study was purified by distillation over CaH 2 .…”
Section: Introductionmentioning
confidence: 99%